Formulasi Losio Emolien dari Ekstrak Etanol Sarang Semut (Myrmecodia pendens) dengan Menggunakan Emulgator Anionik dan Nonionik - Astri Syamsuddin, Iskandar Zulkarnain, Nursiah Hasyim (Jurnal Farmasi dan Ilmu Pengobatan, 2016)
Myrmecodia (Myrmecodia pendens) is an epiphytic plant with several active chemical constituents as antioxidants including flavonoids, tocopherol, and tannins. This research aimed to obtain the formula of emolien lotion of the ethanol extract was obtained by soxhletation method using ethanol 96%. In the initial stage of formulation the emulsifier used was first optimized, then formulated and tested its physical stability, such as other organoleptic test, pH, homogeneity, emulsion type, creaming, dispersiibility, viscosity, and the determination of the type of flow before and after the stressed conditions. The data obtained were processed by anova two replication in Microsoft Excel worksheet 2010. The result of myrmecodia extraction were obtained the rendamen of 26,00078%, while the result of the optimization showed that TEA-Stearat 3-7% and Tween 80-Span 80 5% more stable. The results of stability test showed that the anionic emulsifier formula (TEA-Stearat 3-7%) and nonionic emulsifier (Tween 80-Span 80 5%) were physically stable.